World Flu Day 2024 with One Health Approach in Iran - Parvaneh Mehrbod1*; Behrokh Farahmand1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: The global impact and significance of influenza are profound, from the 1918 Spanish flu pandemic to recent seasonal and avian influenza outbreaks. The ongoing need for international collaboration to control and mitigate the effects of influenza remains crucial. World Flu Day, launched on November 1, 2018, at the Asian-Pacific Centenary Spanish 1918-flu Symposium in Shenzhen, China, aimed to raise public awareness, accelerate scientific research, advocate for the development of a universal influenza vaccine, and strengthen the global political efforts for influenza prevention and control. The main objective of the conference was to cover all aspects of influenza, including epidemiology, vaccination, cross-species outbreaks, and treatments. Conference structure and highlights: The structure of the conference included the history of the Pasteur Institute and its Influenza Department, pathogenesis, epidemiology, vaccination, and treatment of human and avian influenza. The key topics discussed were history of the Pasteur Institute's services, introducing the Influenza Department, pathogenesis and epidemiology of influenza infections in Iran and the region, influenza vaccines from past to present, current clinical status of influenza in humans, herbal remedies for influenza treatment, avian influenza and its risks to humans, and emerging influenza viruses and cross-species outbreaks. Conclusion/impact: The important lessons learned from past influenza outbreaks—including vaccination protocols, treatment strategies, crossspecies outbreaks, and global collaborations—were acknowledged as critical for guiding current and future pandemic preparedness efforts under the One Health approach, contributing substantially to the global fight against influenza.